Large effects of land use conversion on C storage in dry forest ecosystems from Southern South America - Conti, Georgina (2014)
Fil: Conti, Georgina. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Biología Vegetal; Argentina.